2023
DOI: 10.7717/peerj.14654
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of PSMD14 suppresses bladder cancer proliferation by regulating GPX4

Abstract: Objective The aim of this study was to investigate the role of deubiquitinase (DUB) 26S proteasome non-ATPase regulatory subunit 14 (PSMD14) in patients with bladder cancer. Methods From 2016 to 2018, 181 patients diagnosed with primary bladder cancer at the Affiliated Hospital of Qingdao University were recruited. The expression of PSMD14 in bladder cancer tissues was tested by immunochemistry. The association between PSMD14 expression and clinical and pathological data and outcomes of bladder cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Through analysis, we found that many immune-related genes are closely related to the progression of UC to COAD, and PSMD14 has been con rmed to be closely related to the progression of many cancers (19,20,21).…”
Section: Discussionmentioning
confidence: 97%
“…Through analysis, we found that many immune-related genes are closely related to the progression of UC to COAD, and PSMD14 has been con rmed to be closely related to the progression of many cancers (19,20,21).…”
Section: Discussionmentioning
confidence: 97%